2021
DOI: 10.1038/s41598-021-87116-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel, hands-free ultrasound patch for continuous monitoring of quantitative Doppler in the carotid artery

Abstract: Quantitative Doppler ultrasound of the carotid artery has been proposed as an instantaneous surrogate for monitoring rapid changes in left ventricular output. Tracking immediate changes in the arterial Doppler spectrogram has value in acute care settings such as the emergency department, operating room and critical care units. We report a novel, hands-free, continuous-wave Doppler ultrasound patch that adheres to the neck and tracks Doppler blood flow metrics in the common carotid artery using an automated alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 38 publications
0
44
0
1
Order By: Relevance
“…Fourth, the Doppler angle of insonation employed by the ultrasound patch is estimated to be 60°. In vitro, we have shown that this estimation introduces a clinically small, fixed error into the VTI calculation that is mitigated when the VTI is referenced to its baseline value 19 . Because the ultrasound patch is adhered to the neck, the angle of insonation remains relatively constant throughout the study and small, absolute velocity error is accounted for.…”
Section: Limitationsmentioning
confidence: 98%
See 3 more Smart Citations
“…Fourth, the Doppler angle of insonation employed by the ultrasound patch is estimated to be 60°. In vitro, we have shown that this estimation introduces a clinically small, fixed error into the VTI calculation that is mitigated when the VTI is referenced to its baseline value 19 . Because the ultrasound patch is adhered to the neck, the angle of insonation remains relatively constant throughout the study and small, absolute velocity error is accounted for.…”
Section: Limitationsmentioning
confidence: 98%
“…In vitro, we have shown that this estimation introduces a clinically small, fixed error into the VTI calculation that is mitigated when the VTI is referenced to its baseline value. 19 Because the ultrasound patch is adhered to the neck, the angle of insonation remains relatively constant throughout the study and small, absolute velocity error is accounted for. Importantly, however, should the carotid artery move relative to the adhered transducer face (eg, significant head and neck movement), erroneous VTI change is introduced.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…as neck position does not change during the maneuver (34). Also, the device averages cardiac cycles over many seconds which attenuates handheld sampling variability (30,31).…”
Section: Clinical Considerations and Description Of The Wearable Dopplermentioning
confidence: 99%